PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA PEGAWAI PADA DINAS KEPEMUDAAN DAN OLAHRAGA KOTA TANGERANG SELATAN - Rendi Priyana; Fahmi Susanti (Program Studi Akuntansi Fakultas Ekonomi dan BisnisUniversitas Nusa Nipa, 2025)
This study aims to de.te.rmine. the. partial and simultane.ous influe.nce. be.twe.e.n Job Stre.ss and Job Conflict on E.mploye.e. Pe.rformance. at the. Youth and Sports Se.rvice. of South Tange.rang City. The. me.thod use.d in this re.se.arch is quantitative. with a causal associative. approach and saturate.d sampling te.chnique. with a population and sample. of 82 re.sponde.nts. The. analysis me.thod use.d in this re.se.arch is line.ar re.gre.ssion analysis, corre.lation coe.fficie.nt analysis, coe.fficie.nt of de.te.rmination analysis, and hypothe.sis te.sting. Base.d on the. re.sults of the. study, work stre.ss has a positive. and significant e.ffe.ct on e.mploye.e. pe.rformance., this is e.vide.nce.d by the. line.ar re.gre.ssion e.quation Y = 14.671 + 0.192 (X1), the. corre.lation coe.fficie.nt value. is obtaine.d at 0.160, the. le.ve.l of corre.lation be.twe.e.n variable.s is inte.rpre.te.d as ve.ry low, the. hypothe.sis te.st obtaine.d the. tcount value. < ttable. or (1.453 < 1.664) and the. value. (sig) 0.150> 0.05, so the.re. is no partial and insignificant influe.nce. be.twe.e.n work stre.ss on e.mploye.e. pe.rformance.. The. re.sults of re.se.arch on work conflict have. a positive. and significant e.ffe.ct on e.mploye.e. pe.rformance., this is e.vide.nce.d by the. re.sults of line.ar re.gre.ssion Y = 2.889 + 0.844 (X2), the. corre.lation coe.fficie.nt value. obtaine.d is 0.709, the. le.ve.l of corre.lation be.twe.e.n variable.s is inte.rpre.te.d as strong, the. hypothe.sis te.st obtaine.d tcount> ttable. or (8.997> 1.664) and the. value. (sig) 0.000 <0.05, so the.re. is a partial and significant influe.nce. be.twe.e.n work conflict on e.mploye.e. pe.rformance.. Furthe.rmore., the. re.sults of re.se.arch on work stre.ss and work conflict simultane.ously have. a positive. and significant e.ffe.ct on e.mploye.e. pe.rformance., this is e.vide.nce.d by the. line.ar re.gre.ssion e.quation Y = 3.904 + -0.083X1 + 0.870X2, the. corre.lation coe.fficie.nt value. is obtaine.d at 0.712, the. le.ve.l of corre.lation be.twe.e.n variable.s is inte.rpre.te.d as strong. the. coe.fficie.nt of de.te.rmination is 50.7% while. the. re.maining 49.3% is influe.nce.d by othe.r factors, the. hypothe.sis te.st obtaine.d Fhitung> Ftabe.l or (40.663> 3.11) the.n Ho3 is re.je.cte.d and Ha3 is acce.pte.d.